2020
DOI: 10.3390/s21010122
|View full text |Cite
|
Sign up to set email alerts
|

AF-SENet: Classification of Cancer in Cervical Tissue Pathological Images Based on Fusing Deep Convolution Features

Abstract: Cervical cancer is the fourth most common cancer in the world. Whole-slide images (WSIs) are an important standard for the diagnosis of cervical cancer. Missed diagnoses and misdiagnoses often occur due to the high similarity in pathological cervical images, the large number of readings, the long reading time, and the insufficient experience levels of pathologists. Existing models have insufficient feature extraction and representation capabilities, and they suffer from insufficient pathological classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…They showed that the accuracy of normal-cancer classification was high (99.64%), but the accuracy of the LSIL-HSIL classification was 76.34%. A recent study that classified cervical tissue pathological images based on fusing deep convolution features has been published [ 37 ]. The researchers analyzed the dataset comprising small-sized images cropped from 468 WSIs, including those of normal tissues, LSIL, HSIL, and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the accuracy of normal-cancer classification was high (99.64%), but the accuracy of the LSIL-HSIL classification was 76.34%. A recent study that classified cervical tissue pathological images based on fusing deep convolution features has been published [ 37 ]. The researchers analyzed the dataset comprising small-sized images cropped from 468 WSIs, including those of normal tissues, LSIL, HSIL, and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus we decided to do exploratory research with the following different fusion strategies: (1) On the basis of different pre-training models, we use all convolutional layers to realize feature extraction and fusion, as shown in Fig. 6 , fusion strategy 1 [ 48 ]. (2) On the basis of the aforementioned strategy, we abandon InceptionRensENetV2 as the feature extractor, and use the partial convolutional layers of the other three pre-training models to extract and fuse features, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…To better evaluate the reliability and generalization ability of models, in this paper, we use the receiver operating characteristic (ROC) curve to judge the performance of our built classification models and the area under ROC curve (AUC) to verify the generalization ability of the models in a more intuitive way [ 12 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…In another study, Huang et al [ 23 ] suggest extracting deep convolutional features by fine-tuning pre-trained deep network models, including ResNet-50V2, DenseNet-121, InceptionV3, VGG19 Net, and Inception ResNet, and then local binary patterns and a histogram of the oriented gradient are used to extract traditional image features. The serial fusion effect of the deep features extracted by ResNet-50V2 and DenseNet-121 (C5) is the best, with the average classification accuracy reaching 95.33%, which is 1.07% higher than ResNet-50V2 and 1.05% higher than DenseNet-121.…”
Section: Review Of Studymentioning
confidence: 99%
“…Furthermore, the recognition ability is significantly improved to 90.89%, which is 2.88% higher than ResNet-50V2 and 2.1% higher than DenseNet-121. Thus, this method significantly improves the accuracy and generalisation ability of pathological cervical whole slice image (WSI) recognition by fusing deep features [ 23 ]. Mulmule and Kanphade [ 24 ] proposed method that employs adaptive fuzzy k-means clustering to separate cell from the unwanted background of the pathological Pap smear image.…”
Section: Review Of Studymentioning
confidence: 99%